1997
DOI: 10.1210/jcem.82.11.4371
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin Expression in Human Pituitary Gland and Pituitary Adenoma

Abstract: Urocortin is a recently identified neuropeptide of the CRF family in the mammalian brain, but its expression in human tissue has been little studied. In this study, we examined urocortin expression in human anterior pituitary gland and pituitary adenomas by RIA, high performance liquid chromatography, immunohistochemistry, messenger ribonucleic acid (mRNA) in situ hybridization, and reverse transcriptase-PCR. Immunoreactive urocortin concentrations in normal pituitary tissue extract were 103.25 +/- 39.05 ng/g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 19 publications
1
45
0
Order By: Relevance
“…Other groups have also detected urocortin mRNA in rat pituitary (Wong et al 1996, Iino et al 1997. These findings would account for the hCRF-BP ligand activity which we detected in the fore and rear cerebral regions, the thalamic region, the pituitary and, perhaps, the brainstem (which is innervated by projections arising in the EW nucleus).…”
Section: Discussionsupporting
confidence: 71%
“…Other groups have also detected urocortin mRNA in rat pituitary (Wong et al 1996, Iino et al 1997. These findings would account for the hCRF-BP ligand activity which we detected in the fore and rear cerebral regions, the thalamic region, the pituitary and, perhaps, the brainstem (which is innervated by projections arising in the EW nucleus).…”
Section: Discussionsupporting
confidence: 71%
“…The highest density of urocortin innervation is observed in the lateral septum and the dorsal raphe nucleus. In a recent study, urocortin immunoreactive cells, as well as urocortin mRNA, were found in human anterior pituitary suggesting that urocortin may have a paracrine or autocrine role in the production and/or secretion of adrenohypophysial hormones (Iino et al 1997). Urocortin binds with equal affinity to both CRF receptor subtypes, but possesses much higher affinity for CRF 2 receptors than does CRF and is found in brain regions distinct from CRF.…”
Section: Corticotropin-releasing Factor and Stressmentioning
confidence: 98%
“…Following antibodies were used: the polyclonal antibodies to GH (1:800; Dakopatts, Glostrup, Denmark), ACTH (1:1600; Dakopatts), CRF (1:1000) [18], Ucn1 (1:1000) [12,19], Ucn3 (1:1000) [13], vasopressin V1b receptor (1:100, 2 µg/ mL; Santa Cruz Biotechnology, Inc., Santa Cruz, CA, USA) and monoclonal antibodies to prolactin (1:1000; Immunotech, Marseille, France), β-subunit of LH (1:1000; Immunotech), FSH (1:1000; Immunotech), TSH (1:100; Chemicon, Temecula, CA), Ki-67, clone MIB-1 (1:100, Lot.012; DAKO, Kyoto, Japan) and CAM5.2 (Becton Dickinson, San Jose, CA) [20]. The antibodies against CRF, Ucn1 and Ucn3 showed no significant cross-reaction with other CRF family peptides, respectively [11][12][13]19].…”
Section: Histological Analysismentioning
confidence: 99%